2011
DOI: 10.1021/jm1016208
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Pharmacological Characterization of Fluorescent Peptides for Imaging Human V1b Vasopressin or Oxytocin Receptors

Abstract: Among the four known vasopressin and oxytocin receptors, the specific localization of the V1b isoform is poorly described due to the lack of selective pharmacological tools. In an attempt to address this need, we decided to design, synthesize and characterize fluorescent selective V1b analogues. Starting with the selective V1b agonist, [deamino-Cys1, Leu4, Lys8]vasopressin (d[Leu4,Lys8]VP) synthesized earlier, we added blue, green or red fluorophores to the lysine residue at position 8, either directly or by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 60 publications
(205 reference statements)
0
26
0
Order By: Relevance
“…These pharmacological properties of terlipressin seem beneficial for the treatment of septic shock. Compared with the defined clinical applications of AVP agonists directed to V1a and V2 receptors, the clinical utility of V1b receptor agonists remains to be clarified, although synthetic ligands against V1b receptors have been developed recently and knowledge is accumulating (98,323).…”
Section: A Avp and Its Analogsmentioning
confidence: 99%
“…These pharmacological properties of terlipressin seem beneficial for the treatment of septic shock. Compared with the defined clinical applications of AVP agonists directed to V1a and V2 receptors, the clinical utility of V1b receptor agonists remains to be clarified, although synthetic ligands against V1b receptors have been developed recently and knowledge is accumulating (98,323).…”
Section: A Avp and Its Analogsmentioning
confidence: 99%
“…Although many different fluorophores have been effectively used to generate useful fluorescent ligands the main classes of fluorophores used have been the BODIPY series (Allen et al, 2000;Baker et al, 2011;Daly et al, 2010;Tomasch et al, 2012b;Vernall et al, 2012), the Alexa series (Arttamangkul et al, 2000;Brand et al, 2008;Corbani et al, 2011;Morishima et al, 2010) and rhodamine derivatives (Castro et al, 2005;Daly et al, 2010;Guo et al, 2012). Fluorescent ligands containing these fluorophores have been effectively used in many of the techniques detailed below with the exception of certain time-resolved fluorescence resonance energy transfer (TR-FRET) studies in which europium linked fluorescent ligands were developed to provide a signal with a long fluorescence lifetime (Albizu et al, 2010).…”
Section: What Are Fluorescent Ligands?mentioning
confidence: 99%
“…To perform useful microscopy studies, a fluorescent ligand for a GPCR needs to show discrete plasma membrane binding which can be blocked by an unlabelled ligand, and low levels of non-specific binding (including intracellular fluorescence). There are many examples in the literature of fluorescent ligands with good imaging properties, including those for the vasopressin and oxytocin receptors (Corbani et al, 2011), kappa opioid receptor (Houghten et al, 2004), b 2 adrenergic receptor (Baker et al, 2011), adenosine-A 3 receptor and the leukotriene B 4 receptor (Sabirsh et al, 2005). Recent work in our laboratory has focused on the development of fluorescent ligands for the adenosine receptors with improved imaging properties.…”
Section: Required Properties Of a Fluorescent Ligandmentioning
confidence: 99%
“…First, the use of a specific antibody directed against tyrosine hydroxylase (TH) showed that the amount of positively stained cells reached 93 Ϯ 5% (three distinct cultures) (data not shown), suggesting that our primary culture mainly consists in chromaffin cells. We then took advantage of our recently characterized V1b-specific fluorescent ligand, d[Leu 4 -(Lys-Alexa647) 8 ]VP, to quantify the V1b-expressing cells (24). We observed that 58 Ϯ 2% of TH immunostained cells were labeled with d[Leu 4 -(Lys-Alexa647) 8 (Fig.…”
Section: Avp and Crh Synergistically Regulate Catecholamine Release Fmentioning
confidence: 99%
“…After 2 d of culture, the adherent cells were incubated with the fluorescent agonist d[Leu 4 -(Lys-Alexa647) 8 ]VP at 150 nM in the presence of 100 nM the selective OT antagonist SR126768A for 2 h at 12 C as previously described (24). The incubations were realized in the presence or absence of an excess of AVP to determine nonspecific labeling.…”
Section: Characterization Of V1b and Crhr1 Receptors In The Bovine Admentioning
confidence: 99%